2001
DOI: 10.1046/j.1440-1614.2001.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Scan in Somatization Disorder Patients: An Exploratory Study of Eleven Cases

Abstract: A proportion of SD patients may present hypoperfusion in SPECT images, uni- or bilaterally, in different brain areas. Possible aetiological explanations for this finding are discussed. Controlled studies are necessary to confirm or refute this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…Advances in neural imaging may enhance our understanding of the interface between somatization disorder and functional somatic syndromes. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Advances in neural imaging may enhance our understanding of the interface between somatization disorder and functional somatic syndromes. 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Brain structural and functional alterations related to SD have been explored with neuroimaging techniques. For example, a single photon emission computed tomography study of patients with SD described hypoperfusion, primarily in the frontal, prefrontal, temporoparietal, and cerebellar areas (Garcia-Campayo et al, 2001). Also, in a positron emission tomography scanning study, somatization accompanied by anxiety was shown to be associated with decreased metabolism in brain regions, such as the ventrolateral prefrontal cortex, ventral anterior cingulate cortex (ACC) , and anterior insular gyrus (Brody et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Like functional cognitive deficits, functional brain changes have not only been described in psychiatric disorders with an organic or "endogenous" origin, but also in conditions perceived as "psychogenic", such as somatization disorder. Hypoperfusion in several brain regions (cerebellum, temporoparietal, frontal, and prefrontal areas), predominantly in the nondominant hemisphere, was demonstrated in SPECT imaging of 11 patients with somatization disorder (50). A F-18 FDG PET study of 10 female patients with severe somatization revealed reductions in glucose metabolism in the caudate nuclei on both sides, in the left putamen, and the right precentral gyrus (51).…”
Section: Discussionmentioning
confidence: 99%